Perencanaan Dana Pensiun Dan Pendidikan Berbasis Syariah: Pendekatan Strategi Untuk Kesejahteraan Masa Depan - Nadiah Ulfatun Hasanah; Rini Puji Astuti; Indana Zulfa Azizah (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Retirement and education planning is an important part of family financial management that aims to achieve sustainable prosperity in the future. From an Islamic perspective, financial planning should be done in compliance with sharia principles that prohibit riba, maysir and gharar. The sharia approach in financial planning includes the use of halal instruments such as sharia insurance (takaful), sukuk, and investment in sharia mutual funds that comply with the fatwa of the National Sharia Council⁽¹⁾. This planning also emphasizes the importance of the values of responsibility, justice, and the blessing of wealth in meeting long-term needs such as children's education funds and family pension funds⁽²⁾. This study shows that good Islamic financial literacy can encourage Muslim communities to plan their future more strategically⁽³⁾. Therefore, strengthening the Islamic financial ecosystem and educating the public are crucial steps in supporting Islamic values-based financial well-being.